Role of copper ions in dielectric and structural investigations of lead– borate glasses. (4th May 2017) - Hana, N. Ait; Taibi, M.; Haddad, M.; Aride, J.; Benkhouja, K.
ABSTRACT: Glasses in the system 0.1CuO-( x -0.1)PbO-(1- x )B2 O3 (0.3≤ x ≤ 0.7) were synthesized by using the melt quench technique. A number of studies such as X-ray diffraction (XRD), differential scanning calorimetry (DSC), fourier-transform infrared (FTIR) and Raman spectroscopy, electron paramagnetic resonance (EPR) and dielectric properties (viz., dielectric constant ϵ΄, dielectric loss and ac conductivity σac ) are employed to characterize the glasses. The amorphous nature of the glasses was confirmed using XRD while the glass transition temperature ( Tg ) of glass samples have been estimated from DSC investigation and found that the Tg decreases with increasing PbO content. Raman and FTIR spectroscopy reveals that when increasing lead ions, the tetrahedral [BO4 ] units are gradually replaced by trigonal [BO3 ] units. The EPR study leads to determine the local site of Cu 2+ ions and its transformation with the Pb content in the studied glasses.